National football league scouting combine tests correlated to national football league player performance - LaPlaca, D. A.; McCullick, B. A. (The Journal of Strength and Conditioning Research, 2020)
The National Football League (NFL) Scouting Combine has been used since 1982 to collect performance information on the top-rated NFL prospects including physical test results from the vertical jump, broad jump, 3 cone drill, shuttle run, 40-yd dash, and bench press. The correlation between NFL Scouting Combine test results and NFL player performance is frequently questioned, and thus this study endeavored to identify significant relationships between NFL Scouting Combine test results and NFL player performance indicators for all offensive and defensive positions, including quarterback (n = 107), fullback (n = 31), running back (n = 228), wide receiver (n = 336), tight end (n = 137), offensive tackle (n = 204), guard (n = 128), center (n = 66), cornerback (n = 276), free safety (n = 92), strong safety (n = 96), outside linebacker (n = 215), inside linebacker (n = 116), defensive end (n = 212), and defensive tackle (n = 223). A Spearman rank-order correlation analysis set at a p of =0.01 and p of = 0.05 level of significance indicated that every offensive and defensive positions had at least 1 NFL Scouting Combine test result that correlated with NFL player performance. These results can be useful for those in charge of making player personnel decisions in the NFL, such as general managers, draft analysts, and scouts by helping them select NFL prospects. Furthermore, these results could inform strength and conditioning coaches in preparing athletes to excel in the NFL.